ANALISIS PERHITUNGAN UPAH LEMBUR KERJA KARYAWAN PADA PT. KDC SAMARINDA - -, Rahmawati - (EKONOMIA, 2019)
PT. KDC Samarinda is in accordance with the Decree of Minister of Manpower and Transmigration of the Republic of Indonesia Number KEP.102 / MEN / VI / 2004 or not.The authors put forward the hypothesis as follows: "that the calculation of overtime work wage at PT. KDC is not in accordance with Minister of Manpower and Transmigration Decree No. KEP.102/MEN/VI/2004."Testing the truth of the hypothesis that has been proposed, the authors compare the calculation of PT. KDC with Decree of Minister of Manpower and Transmigration of the Republic of Indonesia Number KEP.102/ MEN/VI/2004 which result is calculation of PT. KDC is incompatible with Minister of Manpower and Transmigration Decree No. KEP.102/Men/VI/2004 concerning Overtime and Overtime Working Units Article 8 paragraph 2 and article 11.Based on the results of the analysis is considered the calculation of overtime work wage PT. KDC is not in accordance with Minister of Manpower and Transmigration Decree No. KEP.102/MEN/VI/2004 concerning Overtime and Overtime Wages so the author's hypothesis is accepted.